Relationship Between Stress, its Management and Public Well-being in Lithuania: Effect of Sociodemographic and Clinical Factors - Rapolienė, Lolita; Šaparnienė, Diana; Martinkėnas, Arvydas; Dailidienė, Inga; Bredelytė, Aelita; Grigaliūnaitė, Gintarė; Rapolis, Dovydas (Social Welfare: Interdisciplinary Approach, 2024)
The aim of the study was to assess the individual stress intensity and its management in Lithuania in the context of public well-being, concentrating on the effects of socio-demographic and clinical factors on stress intensity. To reach the aim, a quantitative study was conducted. 1137 residents of Lithuania participated in the online survey. A visual analogue scale (1–10, VAS) was used to determine stress intensity and management, and the Arizona Integrative Outcome Scale was used to determine the sense of well-being. The research results indicate that 98% of respondents experience stress with an average stress intensity and only 50% of respondents experience a higher-than-average sense of well-being formed by physical, mental, emotional, social and spiritual state. The measured relationships between stress, socio-demographic and clinical factors suggest that the marital status, education, profession, nature of work, salary, work experience, duration of work and rest, consequences of COVID-19 have the greatest potential for perceived stress. High-intensity stress is prevalent in Lithuania with moderate management. In the study it was identified, that the main tools for reducing stress are communication with supportive persons, daily regimen and sleep, leisure time for a hobby and rehabilitation, avoiding bad habits, appropriate medical SPA treatments or wellness practices.